Application of the SAW Method in Knowing the Level of Student Satisfaction with the Learning System at MAN 1 Model City of Bengkulu - Aisyah Safitri; Leni Natalia Zulita; Aji Sudarsono (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Analysis of the levels of student satisfaction on the quality of education and services at MAN 1 Model Bengkulu City. Where at this time the survey category considering to the large population that can be used as a research unit. Based on the data that can be collected is through questions (questionnaires) to respondents which contains 6 indicators, namely: understanding and expertise of teachers, quality of teachers, teachers providing material according to educational background, curriculum, teachers are always on time, libraries and laboratories that complete, clean rooms and environment, attitude of the teachers, comfortable rooms, facilities, friendly teachers and employees. Complete information. The data used are primary data, question data collection techniques (questionnaires) and documentation as well as secondary data are qualitative and qualitative data analysis using analysis techniques using customer satisfaction index formula. The results of the analysis of respondents or students at MAN 1 model Bengkulu City on the quality of education and services with a score of 0.16 with this score students gave positive responses to the quality of education and services at MAN 1 model Bengkulu City.